1989
DOI: 10.1002/prot.340060107
|View full text |Cite
|
Sign up to set email alerts
|

Computational and site‐specific mutagenesis analyses of the asymmetric charge distribution on calmodulin

Abstract: Calmodulin's calculated electrostatic potential surface is asymmetrically distributed about the molecule. Concentrations of uncompensated negative charge are localized near certain alpha-helices and calcium-binding loops. Further calculations suggest that these charge features of calmodulin can be selectively perturbed by changing clusters of phylogenetically conserved acidic amino acids in helices to lysines. When these cluster charge reversals are actually produced by using cassette-based site-specific mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 81 publications
5
68
0
Order By: Relevance
“…Many of the mutants have differences in charged amino acids which affect their ability to activate selected CaM-dependent enzymes such as MLCK [14,23,24], CaM-dependent protein kinase II [14], phosphorylase kinase [15], and plasma membrane Ca 2÷-ATPase [22]. In our study of CaM mutants we found that the results with the CaM mutants can be divided into three groups, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Many of the mutants have differences in charged amino acids which affect their ability to activate selected CaM-dependent enzymes such as MLCK [14,23,24], CaM-dependent protein kinase II [14], phosphorylase kinase [15], and plasma membrane Ca 2÷-ATPase [22]. In our study of CaM mutants we found that the results with the CaM mutants can be divided into three groups, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 90%
“…Site-directed mutagenesis was used to generate the various mutant calmodulins [13,14]. The mutations are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is inferred from in vitro studies that interactions between CaM and its target enzymes involve structurally overlapping sites on the CaM molecule (29). It has also been speculated that selection pressure for CaM to remain highly conserved across phylogenetic lines is a consequence of tight substrate specificity for CaM-binding sites within CaM-dependent proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Structural information has been derived from examination of calmodulin bound to peptides (Ikura et al, 1992;Meador et al, 1992Meador et al, , 1993 and by analysis of structural modifications of calmodulin on its activation of target enzymes (Craig et al, 1987;Persechini et al, 1989;Weber et al, 1989;Kosk-Kosicka and Bzdega, 1991 ;Cao et al, 1993 light-chain kinase (Ikura et al, 1992;Meador et al, 1992) and Ca*'/calmodulin-dependent protein kinase I1 (Meador et al, 1993). The crystal structure of calmodulin bound to Ca2'-ATPase is not known, but the complex appears to adopt a more extended conformation than the globular shape seen with the other peptides (Kataoka et al, 1991).…”
Section: Discussionmentioning
confidence: 99%